Priorities of intensification of technological development at the meso level of economy - ALEXANYAN, GARRY M.; BANDURIN, ALEXANDER V. (The journal of contemporary issues in business and government, 2020)
The article discusses the priority directions of intensifying the technological development of subjects of the meso-level of the national economy. The list of subjects of the meso-level has been supplemented, enlarged groups of problems of subjects of the meso-level of the national economy in the field of technological development have been identified, and a list of environments has been formulated that determine the atmosphere for the implementation of an engineering project. Based on the analysis of the share of high-tech products in the volume of sales in the domestic and foreign markets, a conclusion was made about the priorities for increasing the intensity of economic activity on the scale of meso-level entities, and a cycle of unifying the problems of development of a meso-level entity was developed.